O bronze final na Serra de Sintra - Cardoso, João Luís (2016)
This paper presents and discusses the results, some of them previously published, of two Late Bonze Age sites at the Sintra mountain range, Penha Verde and Castelo dos Mouros. The late was object of recent excavations witch results are preliminary published in the present article, namely a recipient which decoration characteristics are unknown in the Portuguese territory until now, witch has affinities with the Western Mediterranean, and a ritual deposition of a vessel, intentionally fragmented, probably related to the sacred connotation of Sintra’s mountain range documented since the Chalcolithic.